Tiempo Arrobado - Arauz, Carlos (Revista Universidad de Guayaquil, 1998)
The horse embodies wonder, gazing with the tranquility of power, possessing the majesty of a mountain, mesmerizing with its choreography, an artist in the language of movement, as it strives to bring joy, extending the benefit of the heart, the spirituality of feeling, and concluding that four legs signify aesthetic supremacy over the small human reasoning, tormented by its irresponsible creation.